Have We Progressed Marketing Knowledge? A Meta-Meta-Analysis of Effect Sizes in Marketing Research - Eisend, Martin (Journal of Marketing, 2015)
This study measures the value and progress of knowledge produced in marketing research by using meta-analytic effect sizes as a measure of scientific knowledge. The author combines the results of 176 meta-analyses that include data from more than 7,500 primary studies published between 1918 and 2012. The 1,841 meta-analytic effect sizes show that a considerable body of marketing knowledge has been developed, as expressed by a meta-meta-analytic correlation of .24. This medium-sized effect is as strong or stronger than effects that have been found in compilations of meta-analyses in other, more basic fields of inquiry (e.g., psychology), which shows that marketing is a successful academic discipline. The effect sizes vary across subject areas, with pricing showing the strongest effects, followed by consumer behavior; methods and new product development show the weakest effects. This finding reveals different degrees of knowledge production and varying benchmarks to assess the contribution of future research outcomes in these subject areas. Marketing knowledge follows a discontinuous model of progress: knowledge has increased over time, but at a decreasing rate; the marketing field, which is currently characterized by fragmentation and specialization, has reached a stage of maturity. The findings provide implications for further research regarding how to measure, evaluate, and progress knowledge in marketing.